2018
DOI: 10.1038/s41598-018-30881-0
|View full text |Cite
|
Sign up to set email alerts
|

The effect of Ganoderma lucidum extract on immunological function and identify its anti-tumor immunostimulatory activity based on the biological network

Abstract: Ganoderma lucidum extract (GLE) has shown positive effects for tumor treatment. However, the molecular mechanism of GLE treatment is unknown. In this study, a Hepa1-6-bearing C57 BL/6 mouse model was established to explore the anti-tumor and immunostimulatory activity of GLE treatment. The results showed that GLE effectively inhibited tumor growth without hepatic/renal toxicity and bone marrow suppression, and might enhancing immunological function. Based on the mRNA profiles of GLE treated and untreated mice,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 69 publications
1
10
0
Order By: Relevance
“…5i shows that the liver function indexes (including aspartate aminotransferase and alanine aminotransferase) and renal function indexes (urea nitrogen and creatinine) are within the normal range, and there is no liver or kidney damage. 56 The results fully confirmed that IL-Ti 3 C 2 T x MXene nanosheets have no obvious systemic side effects and have good biological safety.…”
Section: Resultssupporting
confidence: 59%
“…5i shows that the liver function indexes (including aspartate aminotransferase and alanine aminotransferase) and renal function indexes (urea nitrogen and creatinine) are within the normal range, and there is no liver or kidney damage. 56 The results fully confirmed that IL-Ti 3 C 2 T x MXene nanosheets have no obvious systemic side effects and have good biological safety.…”
Section: Resultssupporting
confidence: 59%
“…Meanwhile, we showed that the serum TNF-α level increased in tumor-bearing mice subjected to SF; after the administration of GL-pp, the serum TNF-α level decreased. Some studies found that TNF-α was increased by the Ganoderma lucidum extract complex in the tumor-bearing mice serum ( Zhao et al, 2018b ); polysaccharides from fresh fruiting bodies of Ganoderma lucidum were also able to greatly increase the TNF-α level in macrophage culture cells ( Wang et al, 1997 ). Interestingly, other studies found that triterpene ganoderic acid C1 isolated from Ganoderma lucidum downregulated TNF-α production by macrophages and peripheral blood mononuclear cells (PBMCs) from Crohn’s disease subjects ( Liu et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…PI3K/Akt signaling pathway promotes the growth and invasion of gastric cancer cells by preventing apoptosis [ 25 ]. Ganoderma lucidum extract regulates cytokines and stimulates anti-tumor immunostimulatory activity through cytokine–cytokine receptor interaction [ 26 ]. Nod-like receptor signaling molecules promote glioma angiogenesis by acting on downstream targets such as IL-1 and caspase-1 [ 27 ].…”
Section: Discussionmentioning
confidence: 99%